"Predatory" publishers: to recognize them is to avoid them - Barbaro, Annarita (Journal of EAHIL, 2022)
Predatory publishers, characterised by unscholarly publishing practices, affect all authors and librarians around the globe. These publishers try to exploit the Open Access movement for their own economic interests, soliciting a fee to publish without meeting scholarly publishing standards. Even though this phenomenon has been widespread for several years, there are still many authors who are not sufficiently familiar with this problem. In this article, we discuss the recent initiatives related to the most important tools to help them to recognize and avoid predatory publishers.